A 3'-untranslated region KRAS variant and triple-negative breast cancer: a case-control and genetic analysis - Paranjape, Trupti; Heneghan, Helen; Lindner, Robert; Keane, Florence K.; Hoffman, Aaron; Hollestelle, Antoinette; Dorairaj, Jemima; Geyda, Kimberly; Pelletier, Cory; Nallur, Sunitha; Martens, John Wm; Hooning, Maartje J.; et al. (The lancet. Oncology, 2011)
BACKGROUND: We previously identified a functional variant in a let-7 microRNA (miRNA) complementary site in the 3'-untranslated region of the KRAS oncogene (rs61764370) which is associated with cancer. We aimed to investigate the association of this KRAS variant with breast cancer and tumour biology. - METHODS: We assessed frequency distributions of the KRAS variant in 415 patients with histologically confirmed breast cancer and 457 controls from Connecticut, USA (study group 1) and association of this variant with breast-cancer subtypes in 690 Irish women with known oestrogen receptor (ER), progesterone receptor (PR), and HER2 statuses, and 360 controls (study group 2). We pooled data for study groups 1 and 2 with a cohort of 140 women with triple-negative breast cancer and 113 controls to assess the association of the KRAS variant with triple-negative breast cancer risk, and genome-wide mRNA and specific miRNA expression in patients with triple-negative breast cancer. - FINDINGS: Although frequency distributions of the KRAS variant in study group 1 did not differ between all genotyped individuals, eight (33%) of 24 premenopausal women with ER/PR-negative cancer had the KRAS variant, compared with 27 (13%) of 201 premenopausal controls (p=0.015). In study group 2, the KRAS variant was significantly enriched in women with triple-negative breast cancer (19 [21%] of 90 cases) compared with 64 (13%) of 478 for luminal A, 13 (15%) of 87 for luminal B, and two (6%) of 35 for HER2-positive subgroups (p=0.044). Multivariate analysis in the pooled study groups showed that the KRAS variant was associated with triple-negative breast cancer in premenopausal women (odds ratio 2.307, 95% CI 1.261-4.219, p=0.0067). Gene-expression analysis of triple-negative breast-cancer tumours suggested that KRAS-variant positive tumours have significantly altered gene expression, and are enriched for the luminal progenitor and BRCA1 deficiency signatures. miRNA analysis suggested reduced levels of let-7 miRNA species in KRAS-variant tumours. - INTERPRETATION: The KRAS variant might be a genetic marker for development of triple-negative breast cancer in premenopausal women, and altered gene and miRNA expression signatures should enable molecular and biological stratification of patients with this subgroup of breast cancer. - FUNDING: US National Institutes of Health.
Gesehen am 08.09.2022